PENANGANAN KREDIT MACET PADA BRI CABANG X - Hohedu, Triska Rifanti; Dewi, Any Rustia (University of Merdeka Malang)
The research aims to find out how to deal with bad credit to minimizethe level of NPL at Bank BRI Branch X. Data collected in the form of primarydata and secondary data. The method used is descriptive qualitative. The findings are the process or method of handling bad credit applied to Bank BRI Branch X through internal and external factors can be seen from the figures in the NPL table that handling bad credit is done very well.The results of the study show that the handling of credit at Bank BRIBranch X is carried out by means of Account Officer (AO) prudence in theselection of customers by taking into account various things to consider such as the type of business, character, and credibility of prospective customers. The reason is that the AO's actions in determining customers greatly affect the smoothness of future installment payments. Besides that there are several factors that are beyond the control of AO employees such as increased business, business risks, and the character of the customer itself that cannot be predicted from the start by AO employees. If there is problematic credit, efforts to save credit are also carried out, one of which is the application of the 3R principle and the most frequently applied is restructuring.